Exploring higher order and lower order thinking skills in Indonesian junior high school ELT textbooks - Shabrina, Dinda Bunga; Basthomi, Yazid; Zen, Evynurul Laily (Englisia Journal, 2025)
English textbooks play a pivotal role in supporting English as a Foreign Language (EFL) learning, particularly for junior high school students. Critical thinking skills are essential for enhancing students’ English language proficiency. This study investigates the representation and frequency of Higher-Order Thinking Skills (HOTS) and Lower-Order Thinking Skills (LOTS) in instructional questions within the Grade VII Indonesian ELT textbook (2017 revised edition) published by Kemendikbud, widely used in Indonesian public schools. Employing a qualitative content analysis approach, this study utilized the revised Bloom’s Taxonomy to analyze the data, which were quantified into percentages and frequencies. Findings reveal a higher prevalence of LOTS compared to HOTS in the textbook’s instructional questions. Consequently, teachers are encouraged to creatively adapt these questions to foster critical thinking. Additionally, future textbook authors should prioritize integrating more HOTS-based questions to enhance students’ critical thinking skills in ELT contexts.